Beyond retrospective assessment. Sport event economic impact studies as a management tool for informing event organization - Angel Barajas; Dennis Coates; Patricio Sanchez-Fernandez (European Research on Management and Business Economics (ERMBE), 2016)
Sport event promoters aim to organize them to get the best return on their investment. The purpose of this study is to learn better how to manage the event to maximize the benefit to the host area. Most studies on economic impact of sporting events focus on mega events or look for an impact in medium to large size cities. This study estimates the effect of a two-day event, the Rally Ourense, that takes place in a small town in Spain. Economic impact is estimated based on surveys of spectators and interviews of competitors in the 2009, 2010, and 2011 editions of the rally. The results show that the race has favorable effects, but also suggest that the impact could be increased with some simple changes to the event structure – – Los promotores de eventos deportivos, al organizarlos, se planteancomo objetivo obtener unbuen retorno de su inversión. El propósito de este estudio es conocer mejor cómo gestionar un evento para maximizar el beneficio para la zona que lo acoge. La mayoría de los estudios sobre impacto económico de eventos deportivos se centra en mega-eventos o buscan el impacto en grandes ciudades. Este artículo estima el efecto de un evento de dos días, el Rally de Ourense, que tiene lugar en una peque\~na ciudad en Espa\~na. El impacto económico se estima a partir de encuestas a los espectadores y entrevistas de los competidores en las ediciones del rally 2009, 2010 y 2011. Los resultados muestran que el evento tiene efectos favorables, pero también sugieren que el impacto podría aumentar con algunos cambios sencillos en la estructura del evento.
Keywords: L83; 650; Local event management; Event promotion; Motor sports; Gestión de eventos locales; Promoción de eventos; Deporte de motor